Morphological Analysis of the Arabic WordComparison Between Traditional Arabic Morphological Theory and Modern Morphology (مجلة إحالات, 2026)
In this paper we hope to establish a contrast between the classical Arabic morphologicaltheory and modern morphology regarding the analysis of a word, whether it is a verb or a noun.That by looking at the set of concepts and techniques terms on which each of the two. The purposeof this contrast is not the extent of a theory in relation to the other but rather it is to present two verydifferent models and their difference is not due to the temporal dimension but rather to twocognitive backgrounds that make us deepen the research on morphological analysis.